Lipid Profiles and trans Fatty Acids in Serum Phospholipids of Semi-nomadic Fulani in Northern Nigeria - Glew, Robert H; Chuang, Lu-Te; Berry, Tammy; Okolie, Henry; Crossey, Michael J; Vanderjagt, Dorothy J (Journal of Health, Population and Nutrition, 2010)
The Fulani are semi-nomadic pastoralists of West Africa whose diet, culture, and economy are centred on cattle. Previous studies have shown that the Fulani of northern Nigeria derive 50% of their total calories from fat and 30% of their calories from milk, cheese, yogurt, and butter oil that contain significant amounts of trans fatty acids (TFAs), primarily vaccenic acid, which raise total serum cholesterol and low-density lipoproteincholesterol (LDL-C), and lower high-density lipoprotein-cholesterol (HDL-C). The study was conducted to know how the consumption of relatively large amounts of dairy products by adult Fulani affected the TFA content of their serum phospholipids. Blood samples were collected from 22 male and 29 female Fulani, aged 35-60 years, who were living in rural areas of Gombe state in northeastern Nigeria. The total serum phospholipid fraction was isolated, and its fatty acid composition was determined. Surprisingly, vaccenic acid was not detected, and three other TFAs-18:1-t6, 18:1-t9, and 18:2-t9,t12-together accounted for only 0.16% of the total fatty acid. The mean serum total cholesterol, LDL-C, and triglyceride concentrations of the subjects were within the normal range for populations in developed countries; however, at 32 mg/dL, the mean serum HDL-C concentration of the Fulani males was slightly below the lower limit of the reference range. No correlations were observed between the total TFA percentage or that of the three individual TFAs and any of the parameters of the serum lipid profile. These findings indicate that, with respect to TFAs at least, the fatty acid pattern of the serum phospholipids of Fulani pastoralists does not reflect the high TFA content of their traditional diet. Despite the consumption of rumenic acid-rich dairy products, for unknown reasons, the semi-nomadic Fulani manage to maintain a low level of TFAs in their blood and a relatively healthful serum lipid profile. While the mechanism that accounts for this disconnect between the consumption of TFAs by Fulani pastoralists and the proportion of TFAs in their serum phospholipids is obscure, possibilities include discrimination against rumenic acid during the process of triglyceride synthesis and chylomicron synthesis in the intestine and the preferential oxidation of TFAs by Fulani the people compared to other ethnic groups. Key words: Lipid profile; Fulani; Serum; Trans fatty acids; Nigeria DOI: 10.3329/jhpn.v28i2.4886 J Health Popul Nutr 2010 Apr; 28(2): 159-166